Da revista à televisão: a linguagem folhetinesca sob uma perspectiva transmidiática em A muralha - Borges, Samantha de Oliveira (2016)
This study aims to do the analysis of the narrative A Muralha since it was first published in feuilleton in the magazine O Cruzeiro, occurred between July 1953 and February 1954; its edition book, which was released later the same year and had several editions; and its subsequent adaptation to the homonymous television mini-series in 2000. The common thread of these media transitions is feuilletonistic language, which receives a reinterpretation from the perspective of transmediality. From this, we have proposed that the term transmedia feuilleton, which refers to the ability of a narrative through different media. A Muralha, written by Dinah Silveira de Queiroz, the saga of the Don Braz's family, leader of a group of pioneers inclined to brave Brazil during the late seventeenth century and begin the construction of the city of São Paulo. The TV mini-serie written by Maria Adelaide Amaral, keeps the history of battles and romance, accentuates melodrama and adds characters and themes to the narrative produced by Globo TV. The methodology is based on a comparative analysis of the issues of A Muralha in the magazine O Cruzeiro, the literary work, and the TV mini-serie on DVD. To comprehend the transition from narrative by different media and to reinterpret the feuilletonistic language from the transmedia perspective, a literature review was performed from the dialogic notions to the latest study of currents, as intermediality, the transficionality and transmediality. We have opted for the transmediality and the fundamental result of the work are the contribution to a broader view at transmedia objects, which is not limited only to contemporary narratives, as advocated by Henry Jenkins, author of Convergence Culture proposal. Thus, by a comparative method, we list elements present in feuilletonistic language and which may be considered basic theory transmediality purposes. Finally, an example is this approach through the research object A Muralha, concluding that it is possible to reinterpret the feuilletonistic narrative by the bias of transmediality because the language, both in terms of content and its format, provides the transition their narratives by different media. The expansion of transmedia proposal thus adjust to a context that does not inaugurate the transmedia processes, but promotes an effervescence of its creations.